2001
DOI: 10.1097/00000478-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of the Thyroid Gland

Abstract: Solitary fibrous tumor is a soft tissue neoplasm initially described in the pleura but subsequently reported in a wide variety of locations. The clinical behavior is usually benign, but the existence of aggressive cases has been documented both in the pleura and in extrapleural sites. In this report clinical and pathologic features of seven solitary fibrous tumors of the thyroid gland are presented. Patients' ages ranged from 43 to 64 years (mean 52 years), and tumor sizes varied from 2 to 6 cm. Grossly, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 34 publications
5
68
0
2
Order By: Relevance
“…A review of the literature regarding primary thyroid SFT, showed only 19 cases being reported to date ( [7][8][9][10][11][12][13][14][15][16][17] and Table 3). The morphological and immunohistochemical features of SFT of thyroid, including our cases, are identical to pleural-based solitary fibrous tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature regarding primary thyroid SFT, showed only 19 cases being reported to date ( [7][8][9][10][11][12][13][14][15][16][17] and Table 3). The morphological and immunohistochemical features of SFT of thyroid, including our cases, are identical to pleural-based solitary fibrous tumours.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the thyroid gland, only 19 cases have been reported to date [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Including the patient described here, only 25 patients have been reported in the English literature. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The morphologic, immunohistochemical, and ultrastructural features of the thyroid SFTs are similar to their reported counterparts in other anatomic sites and their clinical outcome is similarly benign.…”
Section: Discussionmentioning
confidence: 93%
“…El tumor fibroso solitario se ha informado en múltiples localizaciones de la economía corporal [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] . Estas lesiones tienen las mismas características citogenéticas, morfológicas e inmunohistoquímicas de las observadas en esta neoplasia en la pleura, por lo cual se ha establecido que se trata de la misma lesión 7 .…”
Section: Características Diagnósticas Características Presentes En Crunclassified
“…Se he reportado en membranas serosas como el peritoneo 40 , ya sea parietal, visceral, retroperitoneo, mesenterio, omento, pared abdominal y sacos herniarios 41 ; también se ha informado en el pericardio, en el cual existen a la fecha 5 casos reportados 42,43 . Otras localizaciones incluyen: meninges, con aproximadamente 30 casos reportados 44 ; cordón espinal, con 12 casos; cavidad oral, con 50 casos 45 ; glándula mamaria, con 50 casos 46 ; tracto gastrointestinal, en el cual se debe hacer su distinción con el tumor estromal gastrointestinal, mediante inmunohistoquímica 47 ; piel, con 10 casos reportados 48 ; riñón, con 20 casos reportados 49 ; tracto genital femenino 50 , y otras 32 localizaciones como órbi-ta, cavidad nasal 51 , espacio pélvico, hígado 52 , mediastino, próstata, glándulas salivales 53 , vías respiratorias superiores, páncreas 54 , corazón, conjuntiva, tiroides 55 , vejiga, amígdalas, vaina carotídea, testículo, entre otros.…”
Section: Características Diagnósticas Características Presentes En Crunclassified